Comparative Study of Mineral Content in Different Varieties of Green Tea: Minerals in Different Green Tea - Bashir, Anila; Sajid, Muhammad; Hamid, Farrukh Siyar; Waheed, Abdul; Bashir, Madiha; Shah, Hussain; Khan, Nadia; Ali, Seemab; Ahmed, Naveed (Biological Sciences - PJSIR, 2021)
Camellia sinensis L. leaves composed of different concentrations of mineral contents play a vital role in human nutrition and health. In this study, locally processed three different green tea varieties i.e. P3, P5 and P9 were used for mineral content determination at National Tea and High Value Crops Research Institute (NTHRI), Shinkiari, Mansehra, Pakistan. Atomic absorption spectrophotometer, flame photometer and Kjehldal apparatus were used for the determination of mineral concentration in all the collected tea samples. Mineral composition of tea samples were identified in the following quantity order: high level of nitrogen (37300 to 41380 mg/L), calcium (515.6 to 522.1 mg/L) and phosphorus (742 to 1220 mg/L) were observed in all tea samples compared to other minerals. Cobalt (Co), molybdenum (Mo), sodium (Na), zinc (Zn), nickel (Ni) and copper (Cu) were highest in P3, while least amount was identified in P5, variety. On the contrary, calcium (Ca), potassium (K) and lead (Pb) contents were maximum in P5, while minimum were in P3. This study revealed that the levels of mineral elements in different varieties of green tea vary from the permissible level but the monitoring of their levels in tea plant is obligatory for future risk measurements.